Tumors in Costa Rica: emphasis on colorectal cancer - Young Leitón, Jean Carlo (2013)
Currently in Costa Rica colorectal cancer has an incidence of 9,49% in men for every 100000 inhabitants, making it the fourth most common cancer in the country, while women ranked sixth in incidence with a 9,22 %. Furthermore, mortality is the fifth most deadly tumor in men and women became the third most common cause of death. This last point is the most significant, because with respect to mortality in women happens to be the fourth leading cause in 2000 to be the third in 2010, up from cervical cancer. The above data are based on studies by the Ministry of Health for the year 2007 (incidence) and 2010 (mortality). Described multiple risk factors, among which are those modifiable as diet, smoking and obesity and non-modifiable as polyposis syndromes and hereditary colon cancer is not associated with these. Usually early symptoms of colorectal cancer are nonspecific, so they show up in more advanced stages of the disease when the clinic is more evident, rectal bleeding being one of the most common symptoms. Treatment will depend on whether the tumor is in early or advanced stages, where appropriate surgery along with adjuvant chemotherapy has shown better in healing rates.